COMBINED SURGERY AND CHEMOTHERAPY FOR CANINE TRANSMISSIBLE VENEREAL TUMOR IN A FEMALE DOG: A CASE REPORT - Jihan Akifah; I Wayan Wirata; I Gusti Ngurah Sudisma (Buletin Veteriner Udayana, 2025)
Canine Transmissible Venereal Tumor (CTVT) is a neoplasia or tumor that can be transmitted through mating and physical contact such as licking, biting, kissing, or touching the tumor area. Canine Transmissible Venereal Tumor is a benign tumor that commonly affects both male and female dogs, with the external genital area as the main location of the tumor. A 1.5-year-old, 13.7 kg, mixed-breed female dog named "Belang" was presented with a bleeding mass on the vulva. Diagnosis was confirmed through physical examination, hematology, and histopathology. The treatment protocol consisted of two phases. First, surgical excision of the mass was performed via episiotomy under xylazine-ketamine anesthesia. Postoperative care included antibiotics (Cefotaxime IV followed by Cefixime PO) and an anti-inflammatory (tolfenamic acid SC). The second phase involved adjuvant chemotherapy with Vincristine sulfate (0.025 mg/kg IV) once weekly, starting three days post-surgery. The patient showed excellent recovery. By day 17, the surgical wound had healed completely, sutures were removed, and the vulva appeared normal with no swelling. The dog resumed normal activity, appetite, and elimination habits. The combination of surgical debulking followed by Vincristine chemotherapy proved to be a highly effective and well-tolerated treatment protocol for CTVT in this case, resulting in rapid and successful resolution.